2018
DOI: 10.1111/clr.13391
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a zoledronate coating on early post‐surgical implant stability and marginal bone resorption in the maxilla—A split‐mouth randomized clinical trial

Abstract: Objectives The objective of this clinical study was to evaluate the effect of a bisphosphonate coating on a titanium implant on the implant stability quotient (ISQ) and the radiographic marginal bone levels at implants during early healing (2–8 weeks). Materials and methods In a randomized double‐blind trial with internal controls, 16 patients received a dental implant coated with zoledronate and one uncoated implant as a control. The coated and uncoated implants which were visually indistinguishable were bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 24 publications
2
16
1
1
Order By: Relevance
“…The null hypothesis of the present study was accepted for implant stability because all groups showed a similar pattern of stability changes during the period of the study without any statistically significant differences among the groups. This is in line with those found by Abtahi et al, 21 who observed no statistically significant differences in ISQ values between the zoledronate coated and uncoated implants during the early healing (8 weeks). In other studies, Abtahi and colleagues using pamidronate/iban-dronate-coated implants in the maxilla, the coated implants showed a larger improvement in fixation over time as measured by ISQ 22,23 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The null hypothesis of the present study was accepted for implant stability because all groups showed a similar pattern of stability changes during the period of the study without any statistically significant differences among the groups. This is in line with those found by Abtahi et al, 21 who observed no statistically significant differences in ISQ values between the zoledronate coated and uncoated implants during the early healing (8 weeks). In other studies, Abtahi and colleagues using pamidronate/iban-dronate-coated implants in the maxilla, the coated implants showed a larger improvement in fixation over time as measured by ISQ 22,23 .…”
Section: Discussionsupporting
confidence: 93%
“…The heterogeneity of the studies investigating the effects of LA of BPs may limit the ability to compare the results of this study and may account for the different results obtained. In the studies of Abtahi et al, [21][22][23] the investigators assessed coated implants against noncoated, while Zuffetti et al, 37,38 evaluated local application of BPs solution. Moreover, the periods of follow-up differed with their time points, the doses of medications and the methods of application also differed as well as implant placement whether submerged or none and jaw sites.…”
Section: Discussionmentioning
confidence: 99%
“…In Abtahi et al [ 26 ] study, zoledronate coated vs uncoated dental implants were compared. These two types of implants were indistinguishable by a blinded operator.…”
Section: Resultsmentioning
confidence: 99%
“…According to Abtahi et al [ 26 ] there are no statistical differences between the use of bisphosphonate coated dental implant or uncoated ones during the early healing phase. Uncoated dental implants just presented more marginal bone loss than test group.…”
Section: Discussionmentioning
confidence: 99%
“…Another study from Jahan Abtahi et al 23 was a splitmouth randomized clinical trial and showed that there is no lack of stability (fixation) in coated implants (solution with 2 mg/ml zoledronic acid) and there is no marginal resorption, in contrast with the non-coated implants.…”
Section: Studies In Humansmentioning
confidence: 99%